The rate and molecular spectrum of mutation are selectively maintained in yeast - Haoxuan Liu; Jianzhi Zhang (Nature Communications, 2021)
How natural selection shapes the rate and molecular spectrum of mutations is debated. Yeast mutation accumulation experiments identify a gene promoting mutagenesis and show stabilizing selection maintaining the mutation rate above the drift barrier. Selection also preserves the mutation spectrum.